Encouraging Sustainable Urban Tourism through Understanding Environmental Knowledge and Supporting Environmentally Friendly Behavior for Urban Tourists in the West Java Region - Riyanto, Slamet (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The problem raised in this study is that tourism not only aims at the number of visitors but also talks about sustainability issues, where uncontrolled urban tourism activities have an impact on urban tourism sustainability in the long term in environmental, social, cultural, economic and health and safety aspects. Research conducted by researchers related to environmentally sustainable urban tourism is still considered very relevant, where the development of tourism concepts can have a long-term impact on the environment, social, cultural, economic and health as well as safety for the present and future for all local communities and tourists who visit. The purpose of this study is to develop a conceptual framework model from our research by testing and analyzing the influence of environmental knowledge on sustainable urban tourism. And the effect of mediating environmentally friendly behavior variables between environmental knowledge and sustainable urban tourism.